Master track of POLARSTERN cruise PS18/4 in 1 sec resolution (zipped, 169 MB) - Hubberten, Hans-Wolfgang (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2025)
Raw data acquired by position sensors on board RV Polarstern during expedition ANT-IX/4 was processed to receive a validated master track which can be used as reference of further expedition data. Processed data are provided as a master track with 1 sec resolution derived from the position sensors' data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.
Keywords: 1 sec resolution